Survival study of multiple antibiotic resistance escherichia coli in water and sediment collected from aquaculture environment - Luk, Jackson Chet Chee (Universiti Malaysia Sarawak, (UNIMAS), 2011)
E. coli is a common inhabitant of the intestinal tract of human and warm-blooded animal. Most are harmless but some strains of E. coli are pathogenic to human. E. coli can be used as indicator of fecal contamination to indicate the present of other more pathogenic microorganisms. Hence, this project study the survival of a MAR E. coli isolated from aquaculture environment. Isolate was tested for the antibiotic resistant pattern and undergoes further identification through molecular studies and biochemical test. E. coli with initial inoculum around 1 x108 CFU/mL was inoculated in broth at 4oC, 25oC, 30oC, 37oC and 40oC for up to 60 days and plate count method was used to determine the concentration (CFU/mL) of the growth of the E. coli. Cell numbers at all temperatures declined over the duration of the experiment. The decline was most pronounced at 37oC that is 5•101 CFU/mL, and was most prolonged at 25oC to 30oC where the numbers of cells were decreased to 2.0•105 and 8•105 CFU/mL, respectively. Survival rate of E. coli was enhanced in the sediment regardless the effect of the temperature. Hence, E. coli in aquaculture environment was able to survive for up to 60 days at all 5 various temperatures.